2009
DOI: 10.1111/j.1365-3040.2009.01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Using combined measurements of gas exchange and chlorophyll fluorescence to estimate parameters of a biochemical C3 photosynthesis model: a critical appraisal and a new integrated approach applied to leaves in a wheat (Triticum aestivum) canopy

Abstract: We appraised the literature and described an approach to estimate the parameters of the Farquhar, von Caemmerer and Berry model using measured CO2 assimilation rate (A) and photosystem II (PSII) electron transport efficiency (F2). The approach uses curve fitting to data of A and F2 at various levels of incident irradiance (Iinc), intercellular CO2 (Ci) and O2. Estimated parameters include day respiration (Rd), conversion efficiency of Iinc into linear electron transport of PSII under limiting light [k2(LL)], e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
345
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(372 citation statements)
references
References 72 publications
(213 reference statements)
10
345
1
1
Order By: Relevance
“…2 across the Chloroplast Membrane May Explain the Decrease of g i with Increasing CO 2 A number of studies (Flexas et al, 2007;Hassiotou et al, 2009;Vrábl et al, 2009;Yin et al, 2009) have shown a similar response to CO 2 as that shown in Figure 6D (i.e. the internal conductance first increases rapidly and then slowly decreases as the CO 2 concentration increases).…”
Section: Leakage Of Hcomentioning
confidence: 76%
“…2 across the Chloroplast Membrane May Explain the Decrease of g i with Increasing CO 2 A number of studies (Flexas et al, 2007;Hassiotou et al, 2009;Vrábl et al, 2009;Yin et al, 2009) have shown a similar response to CO 2 as that shown in Figure 6D (i.e. the internal conductance first increases rapidly and then slowly decreases as the CO 2 concentration increases).…”
Section: Leakage Of Hcomentioning
confidence: 76%
“…The parameters of the FvCB model 39 , were estimated combining gas exchange and chlorophyll fluorescence data according to ref. 69, with some modifications (see Supplementary Methods for details).…”
Section: Methodsmentioning
confidence: 99%
“…We estimated R n during the day after darkening the leaf for at least 30 min. R d was estimated from the light-response curves with the combined GE and CF measurements proposed by Yin et al (2009), named the CF method. This method amended the Kok method (Kok, 1948) by substituting the A/PPFD relationship with A/(PPFD × PSII /4)).…”
Section: Estimation Of Light Respiration and Calculation Of The Effecmentioning
confidence: 99%
“…This method amended the Kok method (Kok, 1948) by substituting the A/PPFD relationship with A/(PPFD × PSII /4)). See Yin et al (2009) for details. The effective quantum yield of CO 2 ( CO 2 , unitless) can be calculated using the estimated α L , R d , together with A net and PPDF as follows:…”
Section: Estimation Of Light Respiration and Calculation Of The Effecmentioning
confidence: 99%